2021
DOI: 10.1038/s41398-021-01601-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of the glucocorticoid receptor gene predicts substance use in adolescence: longitudinal data from over 1000 young individuals

Abstract: Early life stress has been linked to increased methylation of the Nuclear Receptor Subfamily 3 Group C Member 1 (NR3C1) gene, which codes for the glucocorticoid receptor. Moreover, early life stress has been associated with substance use initiation at a younger age, a risk factor for developing substance use disorders. However, no studies to date have investigated whether NR3C1 methylation can predict substance use in young individuals. This study included adolescents 13–14 years of age that reported no histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These data show that FKBP5 and SLC6A4 methylation levels are associated with brain connectivity and structure in regions relevant to adolescent depression. Raffetti et al [ 107 ] reported glucocorticoid receptor ( NR3C1 ) DNA methylation was significantly associated with a higher risk for substance use in adolescents, and NR3C1 exon 1F locus hypermethylation can predict substance use in adolescents. Roberson-Nay et al [ 108 ] investigated DNA methylation from 150 Caucasian monozygotic adolescent twins with or without major depression.…”
Section: Introductionmentioning
confidence: 99%
“…These data show that FKBP5 and SLC6A4 methylation levels are associated with brain connectivity and structure in regions relevant to adolescent depression. Raffetti et al [ 107 ] reported glucocorticoid receptor ( NR3C1 ) DNA methylation was significantly associated with a higher risk for substance use in adolescents, and NR3C1 exon 1F locus hypermethylation can predict substance use in adolescents. Roberson-Nay et al [ 108 ] investigated DNA methylation from 150 Caucasian monozygotic adolescent twins with or without major depression.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the expression of cocaine-induced locomotor sensitization was shown to be dependent on Ca v 1.2 signaling in mice ( 56 ). The NR3C1 gene encodes a glucocorticoid receptor for which downregulation in blood was observed in chronic cocaine users ( 57 ) and its DNAm levels were shown to predict substance use phenotypes in adolescents ( 58 ). Further, brain-specific conditional knock-out of NR3C1 flattened the dose-response curve for cocaine self-administration and reduced behavioral sensitization in an intravenous cocaine self-administration model in mice ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the expression of cocaine-induced locomotor sensitization was shown to be dependent on Ca v 1.2 signaling in mice [55]. The NR3C1 gene encodes a glucocorticoid receptor for which downregulation in blood was observed in chronic cocaine users [56] and its DNAm levels were shown to predict substance use phenotypes in adolescents [57]. Further, brain-specific conditional knock-out of NR3C1 flattened the dose-response curve for cocaine self-administration and reduced behavioral sensitization in an intravenous cocaine self-administration model in mice [58].…”
Section: Discussionmentioning
confidence: 99%